RDLPFC area of the brain encodes sentence polarity: a study using fMRI. - Behroozi, Mehdi; Daliri, Mohammad Reza (Brain Imaging & Behavior, 2015)
In this study, we use functional magnetic resonance imaging (fMRI) in combination with multivoxel pattern analysis to address the question of how mental activities that correspond to sentence polarity (affirmative or negative sentences) are encoded in the brain. This approach allows us to investigate the role of left/right dorsolateral prefrontal cortex (DLPFC) in predicting the neural activity of fMRI associated with sentence polarities. Subjects in the experiment were asked to judge the matching of the presented picture with the meaning of affirmative and negative sentences. Our results highlight the role of RDLPFC in encoding of the related mental activity to sentence polarities such that the right hemisphere (RDLPFC) can predict sentence polarity with high accuracy as compared to the left hemisphere (LDLPFC), and that the negative sentences are decoded with high performance as compared to affirmative sentences from the RDLPFC across subjects. In addition, this experiment's results show that negative sentences involve more syntactic structure than affirmative sentences.